THE ECONOMIC THEORY OF UTILITY APPLIED TO A WEB-BASED SEARCH FOR A ROMANTIC PARTNER - Mantell, Edmund H (Advances in Social Sciences Research Journal, 2017)
There are a few published studies that address the actual behavior of people in scenarios where the subjects must conduct searches of the kind typical of online dating sites. The consensus of the empirical findings seems to be that people tend to stop searching too soon. On the other hand, a very common psychological attitude among those who use online dating sites is a refusal to “settle” for anything less than their ideal partner, or someone very close to it. This paper addresses the question of how a man or a woman should apply the criterion of economic efficiency to choosing a person to pursue for a romantic relationship. The paper applies the mathematical theory of optimal stopping to a situation where a user of a dating website has identified a finite but perhaps very large sample of persons who are potential romantic partners. The paper applies the economic theory of a consumer’s utility function to establish a stopping rule which maximizes the likelihood that the searcher will meet the candidate who maximizes the searcher’s idiosyncratic attitudes.